Functional Compartmentalization of Antibodies in the Central Nervous System During Chronic HIV Infection. (13th April 2022) - Spatola, Marianna; Loos, Carolin; Cizmeci, Deniz; Webb, Nicholas; Gorman, Matthew J; Rossignol, Evan; Shin, Sally; Yuan, Dansu; Fontana, Laura; Mukerji, Shibani S; Lauffenburger, Douglas A; Gabuzda, Dana; et al.
Abstract: The central nervous system (CNS) has emerged as a critical HIV reservoir. Thus, interventions aimed at controlling and eliminating HIV must include CNS-targeted strategies. Given the inaccessibility of the brain, efforts have focused on cerebrospinal fluid (CSF), aimed at defining biomarkers of HIV-disease in the CNS, including HIV-specific antibodies. However, how antibodies traffic between the blood and CNS, and whether specific antibody profiles track with HIV-associated neurocognitive disorders (HAND) remains unclear. Here, we comprehensively profiled HIV-specific antibodies across plasma and CSF from 20 antiretroviral therapy (ART) naive or treated persons with HIV. CSF was populated by IgG1 and IgG3 antibodies, with reduced Fc-effector profiles. While ART improved plasma antibody functional coordination, CSF profiles were unaffected by ART and were unrelated to HAND severity. These data point to a functional sieving of antibodies across the blood-brain barrier, providing previously unappreciated insights for the development of next-generation therapeutics targeting the CNS reservoir. Abstract : The role of HIV-specific antibodies in the brain during chronic infection is unclear. Here we found striking compartmentalization of HIV-specific antibodies, marked by a unique and highly selective enrichment of poorly functional IgG1 and IgG3 antibodies in the CSF.